Influence of steel fibers on the mechanical properties and impact resistance of lightweight geopolymer concrete. (15th October 2017) - Islam, Azizul; Alengaram, U. Johnson; Jumaat, Mohd Zamin; Ghazali, Nurasyiqin Binti; Yusoff, Sumiani; Bashar, Iftekhair Ibnul
Highlights: Effect of uncrushed and crushed OPS on mechanical properties reported. Impact behavior of geopolymer concrete is investigated. Significant improvements in tensile and flexural strengths of FROPSGC observed. Uncrushed OPSGC has better impact resistance compared to crushed OPSGC. Significant improvement in impact energy of FROPSGC. Abstract: The influence of fiber on the mechanical properties and impact resistance of oil palm shell geopolymer concrete (OPSGPC) prepared with ground granulated blast-furnace slag (GGBS) and palm oil fuel ash (POFA) as binders is reported. The mechanical properties of OPSGPC, namely compressive, flexural, splitting tensile strengths, and modulus of elasticity were investigated; impact resistance was found through drop hammer test. The addition of 0.5% steel fibers enhanced the splitting tensile and flexural strengths of fiber reinforced OPSGPC (FROPSGPC) by about 19–38% and 13–44%, respectively compared to the non-fibrous OPSGPC. The FROPSGPC with uncrushed OPS developed higher initial and final impact resistance compared to specimens with crushed OPS. With the addition of 0.5% steel fiber, the first crack load of the geopolymer concrete increased by 1.5–3.5 times compared to the corresponding mixes of OPSGPC without fiber. The ultimate impact energy of most of the OPSGPC and FROPSGPC with uncrushed OPS was found 15–152% higher compared to the corresponding mixes with the crushed OPS aggregate.